2009
DOI: 10.1007/s12275-009-0054-5
|View full text |Cite
|
Sign up to set email alerts
|

Nomenclature of ISCRl elements capable of mobilizing antibiotic resistance genes present in complex class 1 integrons

Abstract: The dissemination of many antibiotic resistance genes has arisen among members of the family Enterobacteriaceae. The dissemination mechanism of these antibiotic resistance genes is closely linked with insertion sequence common region 1 (ISCRl). Thus, caution must be taken in clinical settings to prevent further dissemination of these antibiotic resistance genes. A nomenclature system of ISCRl variants, important for the antibiotic resistance dissemination, was proposed. The proposed system can designate all IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Sequencing revealed that ISCR1 was notable for its close association with quinolone resistance and ␤-lactamase genes (class A and class C). The wide distribution of ISCR1 in MDR Gram-negative bacteria might become a serious threat to the development of future effective antimicrobial therapies, especially since it is almost always found in complex class 1 integrons [17].…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing revealed that ISCR1 was notable for its close association with quinolone resistance and ␤-lactamase genes (class A and class C). The wide distribution of ISCR1 in MDR Gram-negative bacteria might become a serious threat to the development of future effective antimicrobial therapies, especially since it is almost always found in complex class 1 integrons [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, they appear to have become especially prevalent in recent years and there are now some 19 distinct groups based on sequence differences and there is evidence that, like other types of mobile elements, recombination is beginning to generate novel hybrids (Li et al , 2009b). They are also linked to, or embedded in, other types of mobile elements, with perhaps the best example being the common linkage of IS CR1 to class 1 integrons (Sohn et al , 2009), where they act cooperatively to mobilize an increasingly diverse range of antibiotic resistance genes.…”
Section: Elements Within Elementsmentioning
confidence: 99%